A new species of Trichonotus (Perciformes: Trichonotidae) from Somalia and redescription of Trichonotus cyclograptus (Alcock, 1890) with designation of a lectotype - Katayama, Eri; Motomura, Hiroyuki; Endo, Hiromitsu (Zootaxa, 2012)
A new sand diver Trichonotus somaliensis n. sp. (Trichonotidae) is described on the basis of 13 specimens collected offthe coast of Somalia at a depth of 38−78m. The new species is most similar to T. arabicus and T. cyclograptus in lackingelongated anterior dorsal-fin spines and having dark markings on the lateral body surface in males. However, the new spe-cies differs from the others in having the following characters: lateral-line scales 54−57; gill rakers on first arch5−6+18−24; 12–14 blotches on upper half of body in both sexes; first dorsal-fin soft ray length in males 19–28% of stan-dard length; and no free dorsal pterygiophores. Trichonotus cyclograptus, a poorly known species, is redescribed on the basis of the newly-designated lectotype and paralectotypes.